INSECTICIDE SPRAYING IN SOYBEAN PLANTS: DIFFERENT NOZZLES MODELS AND AGROMETEOROLOGICAL CONDITIONS - Costa, Lilian L.; De Moura Aquino, Nathan C. R.; Carneiro, Angela L. C. G.; Almeida, Dieimisson P. [UNESP]; Ferreira, Marcelo Da C. [UNESP] (Soc Brasil Engenharia Agricola, 2018)
The aim of the experiment was to evaluate the quality of the spraying by the spray volume deposit provided by different nozzles models in two agrometeorological conditions of application. Four parameters related to spray quality were evaluated: spray volume deposit, droplet size, surface tension and contact angle. The treatments consisted of three nozzle models (AXI Twin 12002, TTJ 110015 and JAI 120015) and two application times (between 02:00 p.m. and 04:00 p.m. and between 08:00 a.m. and 09:30 a.m.). The spray volume deposit in the upper portion of the soybean plants was similar, but the JAI 120015 nozzle model produces more uniform droplet spectra and is safer than the AXI Twin 12002 and TTJ 110015 due to the highest drift risk. It is necessary to study alternatives that increase spray deposits in the lower portion of the crop, since in this study the distribution uniformity of the mixture in the portions of the soybean plant was low and the agrometeorological conditions interferes in the deposits of the sprayed mixture but is dependent on the selected nozzle model.
Keywords: spray volume deposit; application time; phytosanitary product; application technology